Pre-service teachers' engagement in a cross-curricular television news project: impact on professional identity. Issue 5 (19th October 2016) - Bradshaw, Pete; Younie, Sarah
Abstract : This paper focuses on the impact of pre-service teachers' engagement in the annual BBC News School Report project on their emerging professional identity and on the evidence they provide as part of the process of becoming qualified. The research reported on is drawn from three years of enquiry. Respondents included pre-service teachers themselves, their tutors as representatives of teacher education providers and their mentors as representatives of schools in which they were placed. The methodological approach was interpretative and phenomenological with qualitative and quantitative data being analysed for emergent themes. Two years of evaluations were followed by a third year in which a set of case studies were developed. The research showed that professional identity is enhanced through being in a leading role in respect of curriculum and working with other staff. Through engagement in such projects, this paper moots that pre-service teachers develop richer evidence of emerging professionalism as defined by standards of initial teacher training. Moreover, self-perception of role was modified to one in which they saw themselves, and were seen, as equals to qualified staff rather than subservient to or dependent on them. A new more equal power relationship developed as they took on responsibility for the project. Pre-service teachers' move to become full members of the professional community for which they are training was accelerated.